Rapid endothelialization of small diameter vascular grafts by a bioactive integrin-binding ligand specifically targeting endothelial progenitor cells and endothelial cells. (May 2020) - Hao, Dake; Fan, Yahan; Xiao, Wenwu; Liu, Ruiwu; Pivetti, Christopher; Walimbe, Tanaya; Guo, Fuzheng; Zhang, Xinke; Farmer, Diana L; Wang, Fengshan; Panitch, Alyssa; Lam, Kit S; et al.
Abstract: Establishing and maintaining a healthy endothelium on vascular and intravascular devices is crucial for the prevention of thrombosis and stenosis. Generating a biofunctional surface on vascular devices to recruit endothelial progenitor cells (EPCs) and endothelial cells (ECs) has proven efficient in promoting in situ endothelialization. However, molecules conventionally used for EPC/EC capturing generally lack structural stability, capturing specificity, and biological functionalities, which have limited their applications. Discovery of effective, specific, and structurally stable EPC/EC capturing ligands is desperately needed. Using the high-throughput One-Bead One-Compound combinatorial library screening technology, we recently identified a disulfide cyclic octa-peptide LXW7 (cGRGDdvc), which possesses strong binding affinity and functionality to EPCs/ECs, weak binding to platelets, and no binding to inflammatory cells. Because LXW7 is cyclic and 4 out of the 8 amino acids are unnatural D-amino acids, LXW7 is highly proteolytically stable. In this study, we applied LXW7 to modify small diameter vascular grafts using a Click chemistry approach. In vitro studies demonstrated that LXW7-modified grafts significantly improved EPC attachment, proliferation and endothelial differentiation and suppressed platelet attachment. In a rat carotid artery bypass model, LXW7 modification of the small diameter vascular grafts significantly promoted EPC/EC recruitment and rapidly achieved endothelialization. At 6 weeks after implantation, LXW7-modified grafts retained a high patency of 83%, while the untreated grafts had a low patency of 17%. Our results demonstrate that LXW7 is a potent EPC/EC capturing and platelet suppressing ligand and LXW7-modified vascular grafts rapidly generate a healthy and stable endothelial interface between the graft surface and the circulation to reduce thrombosis and improve patency. Statement of Significance: In this study, One-Bead One-Compound (OBOC) technology has been applied for the first time in discovering bioactive ligands for tissue regeneration applications. Current molecules used to modify artificial vascular grafts generally lack EPC/EC capturing specificity, biological functionalities and structural stability. Using OBOC technology, we identified LXW7, a constitutionally stable disulfide cyclic octa-peptide with strong binding affinity and biological functionality to EPCs/ECs, very weak binding to platelets and no binding to inflammatory cells. These characteristics are crucial for promoting rapid endothelialization to prevent thrombosis and improve patency of vascular grafts. LXW7 coating technology could be applied to a wide range of vascular and intravascular devices, including grafts, stents, cardiac valves, and catheters, where a "living" endothelium and healthy blood interface are needed. Graphical abstract: Image, graphical abstract